Mapy „sugestywne” jako narzędzie propagandy na rzecz ekspansji w niemieckiej myśli geopolitycznej w latach 1919–1945 - Klin, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Geopolitics played a certain role in the ideological-and-political universe of Weimar Germany and the Third Reich. It served as an instrument to convince other states and nations to take certain actions in accordance with allegedly objective laws. In this context, the representatives of geopolitical thought started using “suggestive” maps which, by highlighting selected factors, were supposed to substantiate the necessity of Germany’s expansion and of revision of its borders. This article presents the circumstances in which a big number of “suggestive” maps was published and the assumptions of their authors, and explains the ways in which they exerted persuasive and manipulative influence on their audience. It also includes ten selected maps.
Keywords: Republika Weimarska; III Rzesza; geopolityka; mapy "sugestywne"; propaganda